Cranial magnetic resonance imaging findings in kwashiorkor (2010)
Protein energy malnutrition (PEM) is an important public health problem in the developing countries, although it is becoming uncommon in South West Nigeria. Cerebral changes have been associated with severe PEM. This is study evaluated the neurological changed using Magnetic Reonance Imaging (MRI) in Ibadan south west Nigeria. The 5 children evaluated had a median age of 16 months and all the children had brain changes compatible with cerebral atrophy. In addition two of the children had periventricular white matter changes, while one of these two had mega cisterna magna in addition. Though this study did not re-evalute the brains of these childrenafter nutritional rehabilitation, it is possible that changes are reversible as demostrated in earleir studies.